Akulturasi Tradisi Tionghoa dan Agama Buddha di Vihara Karuna Jala Serpong - Unima Unima (Jurnal Pelita Dharma, 2022)
The problem raised in this study is that the acculturation of Chinese and Buddhist traditions is yet know at Vihara Karuna Jala Serpong. The purpose of this study was to describe the acculturation of the Chinese and Buddhist traditions at Vihara Karuna Jala Serpong. Qualitative method is used in this research. The object and scope of this research is the acculturation of Chinese and Buddhist traditions at Vihara Karuna Jala Serpong, while the reseacrh subjects are temple administrators, people, and surrounding community. Data collection techniques using the methods of obsevation, interviews, and documentation. The data analysis used by the reseacrher is the analysis of the MilesHuberman model analysis which includes data collection, data reduction, data presentation, and drawing conclusions. The results of this study are: (a) the froms of acculturation of Chinese and Buddhist traditions at Vihara Karuna Jala Serpong, namely the from of acculturations activities between Chinese traditions and Buddhism there are player activities commemorations of Chinese and Buddhist holiday as well as various kinds of activities and training there are even form of altars and buildings that support acculturation between Chinese and Buddhist traditions. (b) the effects of acculturation of traditions and Buddhism are positive and negatif. The positive impacts of acculturation between Chinese traditions and Buddhism are: understanding the teachings of the Buddha, strengthening the situation between Chinese tradition and Buddhism, motivating youth, and providing happiness, while the negative impacts are: people do not understand well, do not care about traditions and consider tradition diffcult and complicated.